Strategi Pangkalan Pengawasan Sumber Daya Kelautan Dan Perikanan Batam Dalam Penanganan Illegal Fishing Di Kabupaten Natuna - Titus Prastyo; Nazaki Nazaki; Ardi Putra (Social Issues Quarterly, 2023)
Illegal fishing is a crime of unauthorized fishing that violates marine regulations and violates a country's borders. Illegal fishing cases that occur in Natuna have a negative impact on reduced catches and are very detrimental to the Natuna community in particular. This study aims to determine the strategy of the Batam Marine Resources and Fisheries Monitoring Base in handling illegal fishing in Natuna Regency. This research uses descriptive qualitative research methods, with data collection techniques using analysis, observation and documentation. The results of this research can be seen in the policy direction that policies related to illegal fishing currently prioritize administrative fines, but criminal sanctions can also occur if the violation is fatal. In addition, the strategy of each agency is to strengthen cooperation with each agency authorized to deal with illegal fishing, so that it becomes more effective in handling it. Then related to facilities, currently only rely on surveillance vessels either from the Ministry of Maritime Affairs and Fisheries itself or from other surveillance vessels and the use of detection devices or radar.